Kohesi dan Koherensi dalam Teks Opini Media Online: Telaah Mikro Linguistik dan Wacana Kritis - Misriani, Agita; Murti, Sri; Saputri, Yessa (Universitas Negeri Padang, 2025)
(This study discusses cohesion and coherence in online media opinion texts using a micro-linguistic approach and critical discourse analysis. Although there are quite a lot of studies on opinion texts, there is still a gap in combining micro-linguistic analysis with a critical discourse approach, especially in the context of online media which has its own language characteristics. The purpose of this study is to reveal how elements of cohesion and coherence are built in opinion texts and how the linguistic structure reflects the ideology and power hidden in the text. This study involved 8 opinion texts published in three national online media over the past six months. Data were analyzed using Halliday & Hasan's linguistic analysis instrument for the cohesion aspect and the Fairclough model for critical discourse analysis. The results of the study indicate that lexical and grammatical cohesion are used strategically to build arguments, but coherence of meaning is often formed through hidden ideological assumptions, such as political bias or certain agendas. This study indicates that understanding the micro-linguistic structure in opinion texts is very important for dismantling the practice of power in media discourse, as well as contributing to critical literacy of readers in the digital era.